Human neuronal networks on micro-electrode arrays are a highly robust tool to study disease-specific genotype-phenotype correlations in vitro - Mossink, Britt; Verboven, Anouk H.A.; van Hugte, Eline J.H.; Klein Gunnewiek, Teun M.; Parodi, Giulia; Linda, Katrin; Schoenmaker, Chantal; Kleefstra, Tjitske; Kozicz, Tamas; van Bokhoven, Hans; Schubert, Dirk; Nadif Kasri, Nael; et al. (Stem cell reports, 2021)
Micro-electrode arrays (MEAs) are increasingly used to characterize neuronal network activity of human induced pluripotent stem cell (hiPSC)-derived neurons. Despite their gain in popularity, MEA recordings from hiPSC-derived neuronal networks are not always used to their full potential in respect to experimental design, execution, and data analysis. Therefore, we benchmarked the robustness of MEA-derived neuronal activity patterns from ten healthy individual control lines, and uncover comparable network phenotypes. To achieve standardization, we provide recommendations on experimental design and analysis. With such standardization, MEAs can be used as a reliable platform to distinguish (disease-specific) network phenotypes. In conclusion, we show that MEAs are a powerful and robust tool to uncover functional neuronal network phenotypes from hiPSC-derived neuronal networks, and provide an important resource to advance the hiPSC field toward the use of MEAs for disease phenotyping and drug discovery. •MEAs are a robust tool to model neuronal network functioning•Neuronal networks from different healthy donors show comparable network activity•MEAs are able to distinguish disease-specific neuronal network phenotypes•We provide recommendations to standardize neuronal network recordings on MEA In this article, Mossink and colleagues demonstrate that micro-electrode arrays (MEAs) are a highly robust tool to uncover genotype/phenotype interactions in hiPSC-derived excitatory neuronal networks, and provide an important resource for the design, execution, and analysis of hiPSC-derived neuronal networks studies on MEA.